Newborn Baby Having Birth Weight of 6 Kg. Is It Heaviest Birth Weight Ever Recorded in Bangladesh? - Sultana, Sabina; Ferdous, Sarwar; Hossain, Nurul; Basak, Biplob Kumer (Bangladesh Journal of Child Health, 2010)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI: 10.3329/bjch.v31i1.6074 Bangladesh Journal of Child Health 2007; Vol.31(1-3): 43-45